Eco-Phenomenology: Life, Human Life, Post-Human Life in the Harmony of the Cosmos (Analecta Husserliana, The Yearbook of Phenomenological Research ;, 2018)
This volume presents discussions on a wide range of topics focused on eco-phenomenology and the interdisciplinary investigation of contemporary environmental thought. Starting out with a Tymieniecka Memorial chapter, the book continues with papers on the foundations, theories, readings and philosophical sources of eco-phenomenology. In addition, it examines issues of phenomenological anthropology, ecological perspectives of the human relationship to nature, and phenomenology of the living body and the virtual body. Furthermore, the volume engages in a dialogue with contemporary behavioral sciences on topics such as eco-alienation, sustainability, and the human relationship to the earth in the context of the cosmos. .